Rescue of cystathionine ß -synthase R>C variants by thiol compounds: accessibility of affected residues as a key player - Garcia, Ana Sofia Artur Carreira de Sousa (2017)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2016